An Exploration of Modern Catholic Secondary Education in Shaanxi: The Case of Rose Girls' High School - ZHANG Yingshu, (Journal of Research for Christianity in China (JRCC), 2025)
This study analyzes and summarizes the educational philosophy, institutional innovations, and societal impact of Rose Girls' High School—a renowned Catholic secondary school in Shaanxi during the modern era—through the systematic examination of archival documents, oral histories, and memoirs. It seeks to provide a comprehensive internal and external perspective on Catholic secondary education in China at the time, shedding light on a facet of modern secondary education in Shaanxi and offering insights into the socio-cultural context of Catholic development in the province during the modern period.
Keywords: Rose Girls' High School Modern Shaanxi Society Catholicism